1990
DOI: 10.1038/hdy.1990.107
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in recombination frequency in Arabidopsis

Abstract: Sex differences for rf have been studied in all five chromosomes of the Arabidopsis genome. These differences are strongly segment-specific: in some cases the level of crossing over in male and female meiosis was about the same, though for the majority of segments the rfd is significantly higher than rf9. The data are discussed in the light of the hypothesis about the possible mechanisms of plant sex differences for recombination. The necessity of taking into account the rf sex differences in recombination exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 13 publications
(9 reference statements)
5
22
0
1
Order By: Relevance
“…In previous studies (Vizir and Korol 1990;Giraut et al 2011), it was observed that the M/F overall recombination ratio in A. thaliana is 1.93. Could the extra genetic length of the male genetic maps be due to just an increase in COs from P2, keeping P1 unchanged both for the number of COs and their level of interference?…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies (Vizir and Korol 1990;Giraut et al 2011), it was observed that the M/F overall recombination ratio in A. thaliana is 1.93. Could the extra genetic length of the male genetic maps be due to just an increase in COs from P2, keeping P1 unchanged both for the number of COs and their level of interference?…”
Section: Discussionmentioning
confidence: 99%
“…Assume that recombination reduces gamete fitness, through a reduction of viability (or competitive ability) of crossover combinations, by breaking down coadapted gene complexes (Vizir & Korol, 1990). We propose that reducing recombination frequency in microspore formation could increase fitness in angiosperms whereas reducing recombination frequency in megaspore formation could increase fitness in gymnosperms.…”
Section: Segregation Of Rapd Markersmentioning
confidence: 99%
“…The work of Giraut et al (2011) and others (Vizir and Korol, 1990;Copenhaver et al, 1998;Melamed-Bessudo and Levy, 2012) showed a lack of uniformity and distinct CO landscapes in the male versus female lineage. Recently, CO events were mapped through whole-genome sequencing of F2 plants (Yang et al, 2012), meiotic tetrads (Lu et al, 2012a), and dihaploids (Wijnker et al, 2013) or through sequencing of ecotypes and linkage disequilibrium analysis (Choi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%